Characteristics of halophilic lactic acid bacteria isolated from fermented snakehead fish (Channa striata Bloch) - Nguyen, Phu-Tho; Tran, Thi-My-Ngoc; Nguyen, Huu-Thanh (Agriculture and Natural Resources, 2025)
Importance of the work: This work lays the groundwork for further exploration into the use of halophilic lactic acid bacteria (LAB) in developing high-quality fermented fish products. Objectives: To isolate and characterize halophilic LAB isolated from fermented snakehead fish (Channa striata Bloch), a traditional Vietnamese ‘mam’ product. Materials and Methods: Fermented snakehead samples were collected from local markets and transported to the laboratory under sterile conditions. The fish samples were homogenized in saline solution and serially diluted. Halophilic LAB were isolated by plating onto Man Rogosa Sharpe agar supplemented with 5% NaCl, followed by anaerobic incubation at 30°C for 48 hr. Strains were evaluated for their growth ability in de Man, Rogosa, Sharpe medium containing varying concentrations of NaCl (5–15%), at varying growth temperatures (30–45°C), as well as for their levels of proteolytic activity. Results: In total, 18 LAB strains were isolated from 4 fermented snakehead samples, with identification performed using 16S rRNA gene sequencing. The strain with superior properties, identified as Tetragenococcus halophilus, had signifcant proteolytic activity, crucial for enhancing the flavor and nutritional profile of fermented fish. The isolated strains demonstrated robust growth in high-salinity conditions, specifically at 10% NaCl, with optimal growth observed at 30°C and 35°C. Additionally, most strains had high levels of protein hydrolysis. Main finding: The halophilic LAB Tetragenococcus halophilus FF18.2 was successfully isolated and screened. Due to its ability to thrive in high-salt environments and degrade proteins, the addition of this bacterial strain as a starter culture may contribute to the development of high-quality, safe and potentially more nutritious fermented fish products.